THE COMPARATIVE STUDY OF PUBLIC PARK IN THE PERSPECTIVE OF LANDSCAPE DESIGN IN EAST JAVA PROVINCE - Dwie Retna Suryaningsih; Moch. Thohiron; Faez M. Hassan; Jajuk Herawati; Indarwati Indarwati; Marsela Nova (Yayasan Education and Social Center, 2023)
One way to find out the relative advantages of public parks is by conducting landscape design. The study aims to identify the impact of landscape elements and principles on public parks, To know the application of landscape design elements to public parks, and To find out how to apply landscape principles in public parks. The study was conducted on 10 regional cities in east Java with 3 public parks each, providing 30 public parks from March 2022 to August 2022. The study is achieved with a quantitative and qualitative method in which all data is obtained through direct observations in the field through a questionnaire. The data used in this study is research on landscape performance; landscape design elements and principles are subject to investigation. The observed variable includes 36. Studies take as many as 30 respondents to interviews or fill out questionnaires. Research shows that the Sidoarjo Square, the Unfortunate Square, the Gong Garden, the Apricot Garden, the Torch Park, the Tremiron Garden, and the Bungle Garden take up the first quadrant. The Gersik Square, Stone Square, the Green Town of Stone Park, the Municipal Square, the Old Town Park, Ngronggo Park, Safari 2, Taji Park and Cape Puri occupied the second quadrant. The park occupying Quadrant 3 is Prambanan Gersik, Candra Wilwatikta Park, Kehati Park and Rainbow Park. Quadrant 4 comprises Pancasila Fortress Park, Archway Park, Kennedy park and Mojokerto Square